Comparison between robot-assisted and manual percutaneous coronary intervention - an updated systematic review, meta-analysis, propensity-matched investigation, and trial sequential analysis - Łajczak, Paweł; Ayesha, Ayesha; Sahin, Oguz Kagan; Freeman, Priscilla Isabel; Majeed, Mir Wajid; Righetto, Bruno Branco; Obi, Ogechukwu; Moreno, Gabriel Jacob; Krishna, Mrinal Murali; Mulenga, Kangwa Francis; Finnegan, Emma Ann; Joseph, Meghna; et al. (Cardiovascular Intervention and Therapeutics, 2025)
Robotic-assistance in the percutaneous coronary intervention procedures (R-PCI) has emerged as a novel alternative to manual PCI (M-PCI). However, previous reviews have not incorporated advancements in new devices. Therefore, we aim to present updated results for a comprehensive systematic review and meta-analysis comparing these two modalities.We systematically searched five databases. Clinical studies comparing R-PCI to M-PCI were included. Continuous outcomes were analyzed using a mean difference (MD), while binary outcomes were assessed with odds ratios (ORs) using random-effect models due to anticipated heterogeneity. A total of 10 papers were included. Clinical success for < 20% residual stenosis was higher (OR 7.93 (95% CI 1.02 to 61.68)), while air kerma was lower (MD − 468.61 (95% CI − 718.32 to − 218.90)) in R-PCI procedures. However, procedural time (MD 5.57 (95% CI − 5.69 to 16.84)), fluoroscopy time (MD − 0.30 (95% CI − 2.26 to 1.66)), contrast dose (MD − 6.29 (95% CI − 25.23 to 12.65)), dose area product (MD − 642.57 (95% CI − 2434.20 to 1149.07)), MACE events (OR 0.54 (95% CI 0.15 to 1.96)), and mortality (OR 1.86 (95% CI 0.82 to 4.22)) showed no significant difference between interventions. TSA showed true positive result. Our meta-analysis reveals decreased air kerma in robotic versus manual PCI but fewer statistically significant outcomes overall. Results from this study offer a more comprehensive view of existing evidence compared to previous analyses.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Meta-analysis; PCI; Radiation; Robot; Safety; Trial sequential analysis